2008
DOI: 10.1063/1.2834276
|View full text |Cite
|
Sign up to set email alerts
|

Thermal effects on Farley–Buneman waves at nonzero aspect and flow angles. II. Behavior near threshold

Abstract: Based on the linear dispersion relation of Kissack et al., Phys. Plasmas 15, 022901 (2008), the physical processes that define altitude behavior of marginally stable Farley–Buneman waves in the equatorial electrojet are investigated. The expressions derived for the angular frequency and growth rate are presented in such a way as to make it easy to track the dominant physical processes and to see the relation with earlier work. Two dimensionless parameters are identified that are helpful in showing the transiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 16 publications
1
27
0
Order By: Relevance
“…In our companion paper, 30 we proceed to study threshold behavior of the dispersion relation, focusing on the physical processes that dominate the behavior of Farley-Buneman waves at different altitudes, aspect and flow angles, and wavelengths. In our companion paper, 30 we proceed to study threshold behavior of the dispersion relation, focusing on the physical processes that dominate the behavior of Farley-Buneman waves at different altitudes, aspect and flow angles, and wavelengths.…”
Section: Discussionmentioning
confidence: 99%
“…In our companion paper, 30 we proceed to study threshold behavior of the dispersion relation, focusing on the physical processes that dominate the behavior of Farley-Buneman waves at different altitudes, aspect and flow angles, and wavelengths. In our companion paper, 30 we proceed to study threshold behavior of the dispersion relation, focusing on the physical processes that dominate the behavior of Farley-Buneman waves at different altitudes, aspect and flow angles, and wavelengths.…”
Section: Discussionmentioning
confidence: 99%
“…The other approach, which is based on Grad's set of fluid equations closed at the heat flow level, self‐consistently describes the effects of collisions using Burgers' expressions for collision integrals [ Burgers , 1969]. This approach has been used in work of Kissack et al [1995, 1997, 2008a, 2008b], St.‐Maurice and Kissack [2000], and Kagan and St.‐Maurice [2004].…”
Section: Introductionmentioning
confidence: 99%
“…Many factors conspire to the production of threshold speeds that, however, differ from the isothermal ion-acoustic speed. For one thing, the electrons are neither isothermal nor isotropic (e.g., Sudan, 1995, 1997;Kagan and St.-Maurice, 2004;Kissack et al, 2008). At decameter wavelengths, this conspires to increase the threshold speed of the irregularities, particularly at the lower altitudes (e.g., Kagan and St.-Maurice, 2004).…”
Section: Magnitude Of Saturation Speedmentioning
confidence: 99%
“…For ease of comparison with previous work we continue here to use this parameter even though it has now become clear that a proper calculation of the ion-acoustic speed should include not just electron adiabatic effects mentioned above, but also electron heat flows and thermal diffusion effects. During electron heating events, or in the lower parts of the E-region, these corrections can be substantial (e.g., Sudan, 1995, 1997;Kagan and St.-Maurice, 2004;St.-Maurice and Kissack, 2000;Kissack et al, 1995Kissack et al, , 2008 and we should note that their effects have clearly been observed in the equatorial electrojet (St.-Maurice et al, 2003). An additional problem is that while C S is fairly stable in the equatorial ionosphere, it can vary significantly in the high-latitude region in the presence of electric fields that become so strong that the FB waves themselves will heat the electrons to temperatures well above the ambient atmospheric temperature (e.g., Schlegel and St.-Maurice, 1981;St.-Maurice et al, 1981Wickwar et al, 1981;Jones et al, 1991;Dimant and Milikh, 2003;Milikh and Dimant, 2003;Bahcivan, 2007).…”
Section: Introductionmentioning
confidence: 99%